Reset of inflammatory priming of joint tissue and reduction of the severity of arthritis flares by bromodomain inhibition - Friščić, Jasna; Reinwald, Christiane; Böttcher, Martin; Houtman, Miranda; Euler, Maximilien; Chen, Xi; Walker, Kellie I.; Kirchner, Philipp; Zhu, Honglin; Wirth, Benjamin; Weidner, Daniela; Krüger, René; et al. (Arthritis and Rheumatology, 2023)
Objective: We have recently shown that priming of synovial fibroblasts (SFs) drives arthritis flares. Pathogenic priming of SFs is essentially mediated by epigenetic reprogramming. Bromodomain and extra-terminal motif (BET) proteins translate epigenetic changes into transcription. Here we used a BET inhibitor to target inflammatory tissue priming and reduce flare severity in experimental arthritis. Methods: BALB/c mice were treated intraperitoneally or locally into the paw with I-BET151, which blocks interaction of BET proteins with acetylated histones. Effect of I-BET151 on acute arthritis and/or inflammatory tissue priming was assessed in a model of repeated injections of monosodium urate crystals or zymosan into the paw. I-BET151 was given either from before arthritis induction, at peak inflammation, or after healing of the first arthritis bout. Transcriptomic (RNA-Seq), epigenomic (ATAC-Seq) and functional analysis (invasion, cytokine production, migration, senescence, metabolic flux) was performed on murine and human SFs treated with I-BET151 in vitro or in vivo. Results: Systemic I-BET151 administration did not affect acute inflammation but abolished inflammatory tissue priming and diminished flare severity in both preventive and therapeutic treatment settings. I-BET151 was also effective when applied locally in the joint. BET inhibition also inhibited osteoclast differentiation, while macrophage activation in the joint was not affected. Flare reduction after BET inhibition was mediated, at least in part, by rolling back the primed transcriptional, metabolic and pathogenic phenotype of SFs. Conclusion: Inflammatory tissue priming is dependent on transcriptional regulation by BET proteins, which makes them promising therapeutic targets for preventing arthritis flares in previously affected joints.
CRIS-Team Scopus Importer:2023-01-27